1998
DOI: 10.3109/17453679809002356
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of ankle fractures: A prospective population-based study of 212 cases in Aalborg, Denmark

Abstract: We studied the epidemiology of ankle fractures prospectively during 1 year in a population of about 200,000. The overall incidence rate was 107 fractures per 10(5) person-years. Below the age of 50, ankle fractures were commonest in men. After this age, females became predominant and the age-specific incidence rates decreased in both sexes. The main cause of fracture was falls (87%), on the ground, on stairs or from a height. 137 fractures (55%) occurred in sports, play or other leisure activities. Most patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
1
15

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(176 citation statements)
references
References 9 publications
8
152
1
15
Order By: Relevance
“…Supination external rotation injuries, the most commonly occurring of Lauge-Hansen's categories, were produced in seven experiments [8,12]. In Stage 1, the anterior inferior tibiofibular ligament (AITFL) was injured.…”
Section: Description Of the Lauge-hansen Systemmentioning
confidence: 99%
“…Supination external rotation injuries, the most commonly occurring of Lauge-Hansen's categories, were produced in seven experiments [8,12]. In Stage 1, the anterior inferior tibiofibular ligament (AITFL) was injured.…”
Section: Description Of the Lauge-hansen Systemmentioning
confidence: 99%
“…At follow-up 5 years later, he had no symptoms. 100 000 person-years [3]. Koval et al reported that 14.2% were trimalleolar fractures in the investigation into 33 704 ankle fractures [4].…”
Section: Case Reportmentioning
confidence: 99%
“…The annual incidence of ankle fracture is between 107 and 187 per 100,000 persons [4][5][6] , and around 2% of ankle fractures are open fractures [4] . Ankle fractures usually affect young men and older women, however, below the age of 50 ankle fractures are the commonest in men.…”
Section: Introductionmentioning
confidence: 99%
“…After this age, females become predominant. Alcohol and slippery surfaces are each involved in nearly a third of the cases [6] . Twisting injuries and falls, followed by sports injuries [4] are the most common causes of ankle injuries.…”
Section: Introductionmentioning
confidence: 99%